PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY – TWO STRAY DALAM PEMBELAJARAN MATEMATIKA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) KELAS VIII SMP NEGERI 8 BITUNG - Valensia Lisa Mudami; Anekke Pesik; Ichdar Domu (LPPM Universitas Bina Bangsa, 2023)
The purpose of this research is to find out whether the TS-TS cooperative learning paradigm can have an impact on students' understanding of the subject matter of two-variable linear equations (SPLDV). Only the posttest control group was used in this study design. There may be up to 25 students in class VIII B, the experimental class, and there may be up to 25 students in class VIII C, the control class, who serve as research subjects. randomly selected from three classes. The average control class mastery score was 78.2, while the experimental class was 82.6. Based on the results of the hypothesis evaluation, H0 is rejected and H1 is accepted because t_count = 2.156 and t_table = 1.677, and t_count > t_table. Based on the research findings, students who use the cooperative model type two stay two stray (TS-TS) in the material Linear Equation System with Variables (SPLDV) learn more than students who use the direct instruction model (direct instruction)